2006
DOI: 10.1002/app.24439
|View full text |Cite
|
Sign up to set email alerts
|

Studies on fly‐ash‐filled natural rubber modified with cardanol derivatives: Processability, mechanical properties, fracture morphology, and thermal decomposition characteristics

Abstract: Fly ash, a by-product of thermal power stations, was used as a filler in natural rubber (NR) in presence of 5-10 phr of phosphorylated cardanol prepolymer (PCP) and hexamethylene tetramine cured PCP (PCPHM). The compositions modified with the cardanol-based resins showed lower power consumption for mixing, lower cure time, improved tensile properties and tear strength, and higher thermal stability. Scanning electron microscopy of the fracture surfaces of the tensile-failed specimens showed finer and more unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The results showed that these composites are potential for nonstructural applications. The DMA of fly ash-filled NR modified with cardanol derivatives was carried out by Menon et al 18 The stabilizing effect of lignin filler on NR was examined by Kosikova et al 19 by using DMA. It was observed that the dynamic mechanical properties of NR vulcanisates were considerably improved by the addition of lignin.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that these composites are potential for nonstructural applications. The DMA of fly ash-filled NR modified with cardanol derivatives was carried out by Menon et al 18 The stabilizing effect of lignin filler on NR was examined by Kosikova et al 19 by using DMA. It was observed that the dynamic mechanical properties of NR vulcanisates were considerably improved by the addition of lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Fly Ash (FA), which is produced from coal combustion in power generation plants and primarily consists of inert inorganic materials, has been regarded as a potential substitute for conventional natural fillers, as calcium carbonate (CaCO 3 ), in the plastic industry in several systems: Epoxy [ 1 , 2 , 3 , 4 , 5 ]; polyurethane [ 6 , 7 , 8 ]; polyvinylchloride [ 9 ]; polycarbonate [ 10 ]; polyetheretherketone [ 11 ]; polyethyleneterephtalate [ 12 ]; natural rubber [ 13 ]; thermoplastic elastomers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al reported an increase in the impact properties on the addition of FA in glass fiber/epoxy composites. Menon et al investigated the use of FA as a filler in natural rubber in the presence of 5–10 phr phosphorylated cardanol prepolymer and a hexamethylenetetramine‐cured phosphorylated cardanol prepolymer. This resulted in a higher thermal stability along with an improvement in the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%